INSTITUTIONAL FOUNDATIONS, PARADIGMS OF DIGITAL TRANSFORMATION, AND MECHANISMS OF CIVIC PARTICIPATION IN THE PUBLIC SAFETY SYSTEM OF THE PEOPLE'S REPUBLIC OF CHINA: A COMPREHENSIVE ANALYSIS OF STATE-SOCIETY INSTITUTIONAL INTERACTION IN THE CONTEXT OF MODE - Urazbaev Abatbay Askerbaevich (Journals Park Publishing, 2025)
This study is dedicated to a comprehensive analysis of citizen involvement in ensuring public safety in the People’s Republic of China (PRC), with an emphasis on theoretical foundations and practical applications of legal regulatory mechanisms. The focus is on key legislative acts that govern the interaction between state institutions and public organizations, including such fundamental documents as the PRC laws "On National Security" and "On Counter-Terrorism." The study examines mechanisms of citizen participation, among which the activities of residents’ committees, auxiliary police units, and digital innovations—particularly the social credit system—are evaluated as tools for optimizing public safety. Based on an analysis of statistical data and expert opinions, the functionality and effectiveness of these mechanisms are studied, highlighting their advantages and identifying limitations.
Keywords: Public security, People’s Republic of China, citizen participation, legal regulation, normative acts, residents’ committees, auxiliary police, digital technologies, social credit system, national security, public order, public policy, social stability, comprehensive governance, technological innovations, neighborhood committees, volunteers.